Photoluminescence of Fully Inorganic Colloidal Gold Nanocluster and Their Manipulation Using Surface Charge Effects. Issue 31 (24th June 2021) - Ziefuss, Anna R.; Steenbock, Torben; Benner, Dominik; Plech, Anton; Göttlicher, Jörg; Teubner, Melissa; Grimm‐Lebsanft, Benjamin; Rehbock, Christoph; Comby‐Zerbino, Clothilde; Antoine, Rodolphe; Amans, David; Chakraborty, Indranath; et al.
Abstract: Fully inorganic, colloidal gold nanoclusters (NCs) constitute a new class of nanomaterials that are clearly distinguishable from their commonly studied metal–organic ligand‐capped counterparts. As their synthesis by chemical methods is challenging, details about their optical properties remain widely unknown. In this work, laser fragmentation in liquids is performed to produce fully inorganic and size‐controlled colloidal gold NCs with monomodal particle size distributions and an fcc‐like structure. Results reveal that these NCs exhibit highly pronounced photoluminescence with quantum yields of 2%. The emission behavior of small (2–2.5 nm) and ultrasmall (<1 nm) NCs is significantly different and dominated by either core‐ or surface‐based emission states. It is further verified that emission intensities are a function of the surface charge density, which is easily controllable by the pH of the surrounding medium. This experimentally observed correlation between surface charge and photoluminescence emission intensity is confirmed by density functional theoretical simulations, demonstrating that fully inorganic NCs provide an appropriate material to bridge the gap between experimental and computational studies of NCs. The presented study deepens the understanding of electronic structures in fully inorganic colloidal gold NCs and how to systematically tune their optical properties via surface charge density and particle size. Abstract : The size‐controlled generation of fully inorganic gold nanoclusters is demonstrated by a modern laser‐based synthesis method. These colloidal species exhibit a bright blue photoluminescence, for which the intensity is a direct function of the surface charge density adjustable by the pH of the surrounding medium. Furthermore, these particles offer the opportunity to dedicate photoluminescence to core and surface state transitions.